1962
DOI: 10.1084/jem.116.2.159
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Thymus in Immune Reactions in Rats

Abstract: Rats thymectomized at birth gained weight and otherwise developed normally, but were found to be very susceptible to intercurrent infections. Both Arthus reactivity and delayed hypersensitivity to BSA were markedly impaired in rats thymectomized during the first week of life and significantly impaired in rats thymectomized as late as 3 weeks after birth. The inhibition of Arthus reactivity in thymectomized rats was well correlated with their failure to develop significant titers of precipitating or hemagglutin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0
1

Year Published

1964
1964
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(19 citation statements)
references
References 32 publications
0
18
0
1
Order By: Relevance
“…1, 8, and 10, respectively; center well, normal rat serum. There is complete fusion of the lines formed by ALSo, 1,8, and 10; and partial fusion of the lines formed by ALSB 1 and anti-Ig serum, and by ALSB 8 and anti-Ig serum.…”
Section: Makeup Of Lymphocyte Populations In Txbmmentioning
confidence: 96%
See 1 more Smart Citation
“…1, 8, and 10, respectively; center well, normal rat serum. There is complete fusion of the lines formed by ALSo, 1,8, and 10; and partial fusion of the lines formed by ALSB 1 and anti-Ig serum, and by ALSB 8 and anti-Ig serum.…”
Section: Makeup Of Lymphocyte Populations In Txbmmentioning
confidence: 96%
“…The cells were removed by centrifugation and the sera resterilized by passage through a Millipore membrane. Multiple absorptions (2)(3)(4)(5)(6)(7)(8) were often necessary to completely remove reactivity for any cell type, as judged by indirect immunofluorescence. Absorptions of a single serum with cells from more than one source were done sequentially.…”
mentioning
confidence: 99%
“…Some of the characteristics of the mice thymectomized at birth have also been described in other species subjected to neonatal thymectomy: the rat (15)(16)(17), rabbit (3,10,18), and hamster (19)(20)(21)(22). Particularly interesting are the findings in the thymectomized hamster in which a wasting syndrome associated with hypogammaglobulinemia has been observed (19).…”
mentioning
confidence: 86%
“…However, after learning that early removal of the avian bursa of Fabricius impaired the development of antibody responsiveness, they found that thymectomy of newborn mice and rabbits inhibited lymphocyte development and both cellular and humoral immune responses 22 . Branislav Jankovic and co-workers 23 found that thymectomy of neonatal rats had similar immunological consequences.…”
Section: Cellular Versus Humoral Immunitymentioning
confidence: 95%